Financial crises, exchange rate linkages and uncovered interest-rate parity: Evidence from G7 markets - Dimitris Kenourgios; Dimitrios Dimitriou; Theodore Simos (Economic Modelling, 2017)
This paper examines the dynamic linkages among major exchange rates during the Global Financial Crisis and Eurozone Sovereign Debt Crisis. We extend the previous literature on volatility spillover linkages among the currencies by taking into account the uncovered interest-rate parity hypothesis for 2004–2015. The results indicate that the Canadian Dollar and Great British Pound were affected mainly by the US Dollar across the two crises due to strong financial and economic ties among the three economies, while the Japanese Yen shows evidence of a safe-haven currency. We also provide evidence of varying vulnerability of currencies to both crises, implying increased portfolio diversification benefits, since holding a portfolio with diverse currencies is less subject to systematic risk. These results show that the policy makers need to adopt a stricter form of monetary policy coordination among central banks, since the different vulnerability of currencies across turbulent periods reveals possible non-cooperative monetary policies.